Green synthesis and characterization of copper nanoparticles using Piper retrofractum Vahl extract as bioreductor and capping agent. Issue 8 (August 2020) - Amaliyah, Suci; Pangesti, Dwika Putri; Masruri, Masruri; Sabarudin, Akhmad; Sumitro, Sutiman Bambang
Abstract: The copper nanoparticles (CuNPs) have attracted much attention due to their application in diverse fields. The applications of CuNPs depend on their physical and chemical properties. This study presents the first report for the use of medicinal fruit extract of Piper retrofractum Vahl as an eco-friendly reagent in the synthesis of CuNPs using copper sulfate as a starting material. Piper retrofractum Vahl extract was employed as a bioreductor as well as a capping agent in the formation of CuNPs. The reaction process was assisted by sonication and stirring. The influences of extract concentration, pH, temperature, and reaction time on the size of CuNPs were studied in detail. The morphology and structure of synthesized CuNPs were characterized by UV-Vis, FT-IR, SEM-EDS, TEM, and XRD. The UV-Vis measurement showed the surface plasmon resonance (SPR) peak at 234-255 nm, whereas FTIR characteristic peaks of metal-oxygen (Cu–O) were confirmed in the range 550-570 cm −1 and Cu–O–H bonds led to bending absorptions in the region 870-880 cm −1 . The synthesized CuNPs possess the spherical shapes and high content of copper (70.3%) as confirmed by SEM-EDS. From the TEM micrograph, it can be seen that the particle size distribution of CuNPs has a high uniformity with a size of 2–10 nm under the optimum condition. The crystalline nature of CuNPs as confirmed by XRD showed the crystallinity phase of 26.4%. The synthesized CuNPs have relatively good stability and could inhibit Escherichia coli and Staphylococcus aureus . The results proved that Piper retrofractum Vahl fruit extract could be applied for a greener synthesis of CuNPs with high uniformity of particle sizes. Abstract : Materials science; Materials chemistry; Nanotechnology; Green synthesis, Piper retrofractum, Copper nanoparticles, Plant extract.